Investigation of Mechanical Properties of Recycled ABS Printed with Open Source FDM Printer Integrated with Ultrasound Vibration - Maidin, Shajahan; K. H., Ting; Y.Y., Sim (International Journal of Integrated Engineering, 2022)
Additive Manufacturing (AM) is a process that deposits materials on a platform to form 3D objects layers by layers. One of the downsides of AM is wastage generated during the printing process. Acrylonitrile Butadiene Styrene (ABS) is a popular material used in AM for thermoplastics. This study focused on the feasibility of using recycled ABS for the 3D printing process via an open source Fused Deposition Modeling (FDM) printer. The recycling process began by re-granulating the ABS waste and turning it into a new filament that used to print the test specimens. The experiment was carried out on the mechanical properties of the test specimens, and a comparison was made with the standard ABS specimens. The results showed that recycled ABS could be converted into filaments with an extrusion temperature of 270Â°C and a travel speed of conveyor at 18 mm/s. The results of mechanical properties showed recycled specimen had 32% and 28% reduction in flexural and tensile strength of the printed material, respectively, while an 82% increase in the compression strength due to multiple recycling cycles. With the aid of ultrasound vibration (20 kHz) onto the recycled ABS specimen, the results showed a 53% increase in flexural strength, 59% increase in compression strength and 19% increase in tensile strength comparing with 0 kHz of recycled ABS specimen. Overall, the recycled ABS waste is a viable option for better use of printed materials and, with the aid of ultrasound vibration, it helps to improve the mechanical properties of the recycled ABS.